Neogene rotations of the Chenoua massif, northern Algeria, from remagnetizations - (:unkn) unknown (My University, 2014)
The tectonics of the Chenoua massif suggests block rotations of Neogene nappes associated with the African–European plate convergence. To estimate the extent of these rotations, a Paleomagnetic study on rhyolites and andesites of Langhian–Serravallian age and sandstones of Burdigalian age was carried out on 23 sites (200 specimens). The sites are distributed in the northwestern, southeastern and southern Chenoua massif. One or two components of magnetization, mainly carried by magnetite, pyrrhotite and/or hematite, were isolated in sandstones and volcanics. The sandstone sites reveal magnetizations in sandstones from the Cap Blanc syncline that are post-folding. However, both polarities are found, which is consistent with data from Africa during the Upper Miocene. Clockwise and counterclockwise rotations were recorded, dating back to the Neogene times in volcanics and sediments. From the faulted Cap Blanc syncline counterclockwise rotations of 1 ± 4° to 18 ± 28° around a vertical axis occurred in sediments since the Miocene with respect to Africa. In fact, remagnetizations occurred at several periods of time and in different sites, providing information on the evolution of post-tectonic rotations. Some volcanics record counterclockwise rotations of about 30° since the Miocene, whereas others do not show any significant rotation. This can be explained by the direction of the principal compressive stress axis σ 1 and by lateral extrusions related to an indentation model, in which we expect both clockwise and counterclockwise rotations.
Keywords: African Research